(untitled) (Journal of the Management Sciences, 2024)
As economic challenges pose serious constraints to the Nigeria financial system thus becoming more vicious on the country’s economic and business climate, adjusting the monetary policy of the nation becomes imperative. This study therefore evaluates the impact of monetary policy on economic growth in Nigeria using econometric regression technique of the Ordinary Least Square (OLS). From the result of the OLS, it is observed that monetary policy rate, demand deposit, cash reserve ratio and liquidity ratio have a positive relationship with economic growth. This means that when monetary policy rate, demand deposit, cash reserve ratio and liquidity ratio are increasing, it will bring about more growth in Nigerian economy. On the other hand bank interest rate and exchange rate have a negative impact on economic growth in Nigeria. The findings of the study also show that monetary policy rate, demand deposit, cash reserve ratio, liquidity ratio, bank interest rate and exchange rate are statistically significant in explaining the economic growth in Nigeria. Although, bank interest rate and exchange rate are negative, the negativity has a significant impact in explaining the Nigerian economic growth.Based on the findings the following recommendations are made: The government should as matter of urgency make monetary policy that cuts interest rate. The will help lower the cost of borrowing thus resulting in higher investment activity and the purchase of consumer durables. It is important that the apex financial institution make and implement policies that will encourage demand deposit. This will reduce the cost of handling cash and other associated risks which will lead to increase in financial sector contribution to GDP among others.